2010
DOI: 10.1097/ta.0b013e3181dccea0
|View full text |Cite
|
Sign up to set email alerts
|

Efferent Vagal Nerve Stimulation Attenuates Gut Barrier Injury After Burn: Modulation of Intestinal Occludin Expression

Abstract: Introduction Severe injury can cause intestinal permeability through decreased expression of tight junction proteins, resulting in systemic inflammation. Activation of the parasympathetic nervous system after shock through vagal nerve stimulation is known to have potent anti-inflammatory effects; however, its effects on modulating intestinal barrier function are not fully understood. We postulated that vagal nerve stimulation improves intestinal barrier integrity after severe burn through an efferent signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 33 publications
4
72
0
Order By: Relevance
“…The Tracey laboratories, for example, established that efferent signaling of the vagus nerve acts exclusively via α7nAChR activation in the spleen to regulate systemic cytokine responses to infection in mice (15)(16)(17)(18)(19)(20). Similarly, Costantini and colleagues demonstrated the existence of a similar α7nAChR-dependent regulation of the local inflammatory response in tissues (21)(22)(23)(24)(25)(26)(27). With α7nAChR activation clearly essential to inflammation, not to mention vagus nerve responsiveness and leukocyte function (28,29), we reasoned that it was therefore critical to understand how a human-specific α7nAChR in human leukocytes might influence human leukocyte function, the regulation of its expression and the biological consequences of its expression.…”
Section: Introductionmentioning
confidence: 95%
“…The Tracey laboratories, for example, established that efferent signaling of the vagus nerve acts exclusively via α7nAChR activation in the spleen to regulate systemic cytokine responses to infection in mice (15)(16)(17)(18)(19)(20). Similarly, Costantini and colleagues demonstrated the existence of a similar α7nAChR-dependent regulation of the local inflammatory response in tissues (21)(22)(23)(24)(25)(26)(27). With α7nAChR activation clearly essential to inflammation, not to mention vagus nerve responsiveness and leukocyte function (28,29), we reasoned that it was therefore critical to understand how a human-specific α7nAChR in human leukocytes might influence human leukocyte function, the regulation of its expression and the biological consequences of its expression.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, it is interesting that intestinal permeability have in several observations been found to be controlled by the vagus nerve 101,166 , further supporting participation of nerves in rotavirus disease.…”
Section: Paper II Rotavirus Infection Increases Intestinal Motility Bmentioning
confidence: 99%
“…This phenomenon may be explained by the role of nerves in controlling the gut barrier, and demonstrates the risks with conclusion from cell culture systems, lacking the nerve innervation. The vagus nerve has also been shown to affect the intestinal permeability 100,101 . Indeed, vagus nerve stimulation has been shown to attenuate disruption of tight junction in intestinal epithelium in endotoxemic mice, by a mechanism that seem to involve α7 nicotine acetylcholine receptor (α7 nAchRs) 102 .…”
Section: Paracellular Permeabilitymentioning
confidence: 99%
“…Remarkably, vagotomised rats, do not experience sickness behavior following LPS injection 205 and experimental models have demonstrated that vagus nerve stimulation (VNS) is an effective therapy for attenuating inflammation triggered by endotoxemia 206 . In addition to promoting an anti-inflammatory cholinergic response, VNS also directly improves the integrity of the tight gap junction proteins that regulate intestinal permeability 207 . VNS has also been shown to decrease intestinal permeability and improve the integrity of the blood-brain barrier, both of which would be beneficial following TBI 208,209 .…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%